Huni ng kawayan an activity book design introducing Surat Mangyan to grade 7 students to foster appreciation of Mangyan culture - Caingat, Clariz O. (College of Fine Arts, University of the Philippines Diliman, 2019)
Cultural heritage and history are important as it upholds a people's identity as a nation. It mirrors and forms their ideals, views and goals, and preserves their national honor. Knowledge and understanding of one's own cultural identity and history is an integral part of unity in nation-building. The Ambahan Poetry and Mangyan Syllabic Script are cultural items of the Hanunoo Mangyans which, according to the Mangyan Heritage Center (MHC), are in threat of dying. The Ambahan are poems, which are engraved on the surfaces of bamboos written in the Mangyan Syllabic Script, also known as Surat Mangyan, an ancient writing system which the Hanunoos have been able to preserve up to the present time. Aside from reviving the tradition within the Mangyan community, another dynamic that can help in safeguarding cultural heritage is to introduce it to the people outside the community in order to foster a sense of understanding and appreciation from them. The young generations of lowlanders living in Mansalay Oriental Mindoro, though they interact with the Mangyans in their daily life, seem to have very little knowledge about the culturally-rich past and ancient traditions of their region, particularyly those that originated from the Hanunoo Mangyan community, as can be seen from the results of surveys. Although the traditions are considered to be both culturally significant and in threat of dying. the printed materials that exist related to educating the public about the traditions are very scarce. The few that are currently available contain inadequate and incorrect information, such as the DepEd-issued textbooks currently used in the grade 7 level in public schools, the others are academic papers unfit for grade school classroom use as they are created for an older target audience. This is a problem for the public schools in rural areas, particularly those based in Mindoro because the student are unable to gain quality knowledge regarding the culture of their own region. In line with this, the proposal is concerned with the creating a design of an activity book which can present accurate and sufficient information regarding the Ambahan Poetry and Mangyan Syllabic Script of the Hanunoo Mangyans to the non-Mangyan Grade 7 students of Fe Del Mundo National High School, a public school based in Mansalay, Oriental Mindoro, the municipality wherein majority of the Hanunoos are based. Since the Ambahan Poetry and Surat Mangyans are already integrated in the K-12 DepEd curriculum under MAPEH, the research aims to create a design communication plan which will serve as a supplement to the DepEd-issued MAPEH textbook for Grade 7 students. This activity book aims to broaden the students' knowledge . spark their interest in gaining more insights about the topic, and deepen their appreciation for the culture of the Mangyans which is related to the history of their province as well.